Here's a series the limit of which I want to evaluate:


Here's how I did it. Let's define 3 sequences:

$b_n=\frac{n^2-7n}{n^3+3n^2+n}$, $c_n=\frac{n-\frac{n}{2}}{n^2+4n}$, $d_n=\frac{2}{3n}$

We have $\sum d_n=\frac{2}{3}\sum\frac{1}{n}$ and as $\sum\frac{1}{n}$ is divergent, $\sum d_n$ is also divergent.

So if we prove that for sufficiently large n $d_n \leq c_n$, same for $c_n \leq b_n$ and finally same for $b_n \leq a_n$ then by comparison test we will prove, that $\sum a_n$ is divergent. So let's do this now.

$\sum c_n=\sum\frac{1}{2(n+4)}=\frac{1}{2}\sum\frac{1}{n+4}$

Now let $e_n=\frac{1}{n+4}$. For sufficiently large n we have $\frac{1}{n+\frac{n}{2}}=\frac{2}{3n}=d_n\leq e_n$. So, by comparison test $\sum e_n$ divergent, so that means $\sum c_n$ is also divergent.

$c_n \leq b_n$ because $\frac{n-\frac{n}{2}}{n^2+3n+n} \leq \frac{n-7}{n^2+3n+1}=\frac{n^2-7n}{n^3+3n^2+n}$and $b_n \leq a_n$ is obvious.

So this is it, now we've proven that $\sum a_n$ is divergent. The problem is it took a while and I'm not sure whether my solution is correct. Are there other, simpler ways to solve this problem? Preferably without derivatives and integrals - I haven't covered them in my course yet.


Use the limit comparison test. Let $a_n = \dfrac 1n$ and $$b_n = \frac{(1+\frac{1}{n})^nn^2-7n}{n^3+3n^2+1}.$$

Since $\displaystyle \sum_{n=1}^\infty a_n$ diverges and $\dfrac{a_n}{b_n} \to \dfrac 1e < \infty$, you have that $\displaystyle \sum_{n=1}^\infty b_n$ diverges too.


You can use a simpler approach.


Ok, let's call $b_n=\sum_{n=1}^{\infty}\frac{(1+\frac{1}{n})^nn^2}{n^3+3n^2+1}$ and $c_n=\sum_{n=1}^{\infty}\frac{n}{n^3+3n^2+1}$

$c_n$ converges easily...

And $b_n>\sum_{n=1}^{\infty}\frac{n^2}{n^3+3n^2+1}$, which diverges...

So $a_n$ diverges.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.